Εξ αποστάσεως διδασκαλία ιστορίας της τέχνης μέσω διαδικτυακής εφαρμογής στηριγμένη στο μοντέλο 4ΜΑΤ - Παπαδοπούλου Μαρία; Σοφός Αλιβίζος (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
This article presents an online multimedia application for long distance learning based on the 4MAT model of Bernice McCarthy. Specifically the aim of the article is, through the creation and synthesis of educational material with the help of 4MAT model to investigate a) the usability of it and b) if it can strengthen the motivation of a student who participates in such an education program for the art history discipline. At this point it must be emphasized that the 4MAT model is been applied for first time in long distance learning and at the particular educational field. The results from the evaluation led us to conclude that the 4MAT can be utilized for the creation of an easy to use online multimedia material and it can be used for the teaching of history of art in long distance learning. Also to add the 4MAT model to the teaching models that promotes online long distance learning fulfilling the aims of the research. The focus of the article is on the results of this research in relation to the usability of the model and the ability of the model to motivate.